Urticaria and Angioedema A Comprehensive Review of - Pelin Kartal, Selda; Kutlubay, Zekayi (IntechOpen, 2017)
This book contains the latest advances and scientific knowledge from the leading experts in urticaria and angioedema. The book consists of 15 chapters in which urticaria classification, urticaria etiopathogenesis, urticaria clinics, urticarial syndromes, angioedemas, diagnosis, pathogenesis and pathophysiology of urticaria, and treatment options are discussed. This book also emphasizes on the various laboratory tests necessary for urticarias. One chapter of the book is devoted to comorbidities in chronic spontaneous urticaria. Another chapter is related with pathophysiology and treatment of hereditary angioedema. We are grateful to all the contributors and leading experts for their valuable chapters, which provide an in-depth view of all aspects of the content, backed with the most current literature in the field. We hope that this book will provide interesting knowledge and serve as a comprehensive guide to many physicians dealing with urticaria and angioedemas in their clinical practice.